2018
DOI: 10.1101/455261
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryo-EM structures and functional characterization of the lipid scramblase TMEM16F

Abstract: The lipid scramblase TMEM16F initiates blood coagulation by catalyzing the exposure of phosphatidylserine in platelets. The protein is part of a family of membrane proteins, which encompasses calcium-activated channels for ions and lipids. Here, we reveal features of TMEM16F that underlie its function as lipid scramblase and ion channel. The cryo-EM structures of TMEM16F in Ca 2+ -bound and Ca 2+ -free states display a striking similarity to the scramblingincompetent anion channel TMEM16A, yet with distinct di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 65 publications
2
6
0
Order By: Relevance
“…The rapid decrease of current rendered it difficult to record the reversal potential of wild-type TMEM16F in 1 mM Ca 2+ , because when we switched the bath (equivalent to intracellular solution) from 150 mM NaCl to 15 mM NaCl, the currents recorded from Tmem16ftransfected cells were indistinguishable from currents endogenous to HEK293 cells ( Figure 1-figure supplement 1A, B, C). Consistent with previous reports (6,9), TMEM16F current induced by 15 µM Ca 2+ was selective for Na + over Cl -( Figure 1E).…”
Section: Tmem16f Q559k Shifts Ion Selectivity Towards Clas Intracellusupporting
confidence: 93%
See 4 more Smart Citations
“…The rapid decrease of current rendered it difficult to record the reversal potential of wild-type TMEM16F in 1 mM Ca 2+ , because when we switched the bath (equivalent to intracellular solution) from 150 mM NaCl to 15 mM NaCl, the currents recorded from Tmem16ftransfected cells were indistinguishable from currents endogenous to HEK293 cells ( Figure 1-figure supplement 1A, B, C). Consistent with previous reports (6,9), TMEM16F current induced by 15 µM Ca 2+ was selective for Na + over Cl -( Figure 1E).…”
Section: Tmem16f Q559k Shifts Ion Selectivity Towards Clas Intracellusupporting
confidence: 93%
“…Here, we report that TMEM16F Q559K current persisted with prolonged exposure to high intracellular Ca 2+ . Previous studies have indicated that Q559 faces the ionic permeation pathway and that lysine substitution reduces TMEM16F cation selectivity (6,9), and we now further show that this mutant displays different Na + /Clselectivity in different Ca 2+ concentrations. The difference in ion selectivity did not correlate with alterations of the open states, but instead was regulated by the electrostatic change along the permeation pathway, on which divalent ions (such as Ca 2+ and Zn 2+ ) had more significant impact than monovalent ions.…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations